(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2024)
This article discusses the impact of exporting goods on the economy of a country, the production of high value-added products through deep processing of raw materials in the country and their export. At the same time, the role and importance of goods in the share of exports in the use of resources by developed countries are highlighted.